An Analysis of the Internal Logic of Intangible Cultural Heritage Pyrography Inheritance from the Perspective of Chinese Modernization (Journal of Global Arts Studies, 2025)
Background: In the process of Chinese modernization, cultural inheritance should not only pursue innovation but also remain firmly grounded in the preservation of tradition. Objective: As one of the treasures of intangible cultural heritage, pyrography employs heated tools as brushes and burn marks as ink, inheriting and continuing the spirit of traditional Chinese painting. Methods: From the perspective of traditional Chinese painting theory, this paper traces the origins of pyrography in order to extract the internal logical connotations underlying the inheritance of intangible cultural heritage pyrography, namely “technique as the foundation, law as the standard, and beauty as the purpose.” Here, “technique” refers to the expression of vitality through variations of density, “law” refers to the embodiment of spirit through artistic conception, and “beauty” refers to the realization of value through the integration of techniques. These three dimensions are interconnected and mutually reinforcing. Results: The study finds that only by clarifying the meanings and relationships among these three dimensions can the intrinsic cultural and artistic characteristics of intangible cultural heritage pyrography be effectively preserved. Conclusion: In summary, analyzing the internal logic of pyrography inheritance through the lens of traditional Chinese painting theory can effectively guide the innovative development of intangible cultural heritage pyrography from its cultural roots.
Keywords: Chinese Modernization Process; Pyrography; Chinese Painting Theory; Preservation of Tradition